Structure and temporal dynamics of marine biodiversity in the Terra Nova Bay area (Ross Sea, Antarctica) analysed through DNA barcoding and metabarcoding: A standardized and systematic approach for the construction of a “DNA Barcode” library. - CECCHETTO, MATTEO (Università degli studi di Genova, 2021)
Aims and structure of the thesis: The firs objective of this thesis consisted in the quantification of the reference library completeness for the Cytochrome c oxidase subunit I (COI) barcode of metazoan species occurring in the Ross Sea MPA and in identifying which taxonomic groups in the last decades were investigated by using “DNA barcode” techniques performed in the Southern Ocean. In order to do that, all the available sequence data on major public repositories were gathered and analyzed. A collection of COI sequences amplified from specimen of the Italian National Antarctic Museum (MNA) was produced and aggregated to the latter to assemble the first global Ross Sea reference library of metazoan COI barcoding sequences. The potentialities of “DNA metabarcoding” techniques applied to the analysis of Antarctic biological communities were also evaluated in Terra Nova Bay (TNB) by focusing on the development of macrozoobenthic pioneering communities colonizing artificial structures over a period of three years and on nanoplankton temporal short-term dynamics in two consecutive years. These studies were conducted using innovative sampling methodologies and experiments and differed not only for the investigated community, but also for the sampling frequency, timing and study purposes. Due to the peculiarities of the three analyses, these will be detailed in three separate chapters. Each chapter is composed by its specific “Introduction” to the concepts discussed in that study, followed by a section on “Materials and Methods” and a joint section with the “Results and Discussion”. Considering that the different chapters, notwithstanding the fact that they pertain to the same, general topic of research, greatly differs in the overall design, as mentioned earlier, no general Discussion for the entire thesis was produced. Instead, an Introduction, discussing the most general topics covered by the entire thesis, is presented at first (i.e. the “Thesis Introduction”), whereas the thesis’ Conclusions, considering all the ...